Studies on Applicability of Poly electrolyte Complex of Vancomycin Hydrochloride for Colon Targeting Beads Using Statistical Optimization (Asian Journal of Pharmaceutics (AJP), 2019)
The present study was initiated to develop colon targeted enteric coated hard capsule containing chitosan-basedpolyelectrolyte complex (PEC) beads of vancomycin HCl 500 mg. The chitosan-based PEC beads were developmentand optimized using 32-full factorial design based on two independent factors were evaluated, each at three levels forall nine possible combinations. The PEC beads were prepared by an ionic gelation method using positively chargedchitosan and negatively charged hupu gum. The vancomycin HCl is an orally administered amphoteric glycol peptides,an antimicrobial substance used in the treatment of enterocolitis caused by Staphylococcus aureus and antibioticassociatedwith pseudomembrane colitis caused by Clostridium difficile. Hence, localization of the drug at its site ofaction is more useful. The pharmacokinetic parameters of the drug also offer feasibility for colon-specific drug deliveryand were developed with a view to have lag time 4–6 h, controlled release in the colon over a period of 16–20 h. Thefinal optimized formulation is further subjected to enteric coating using Eudragit-S100 and subjected to in vitro studies.The optimized formulation showed ˂12% drug release during lag time, 91.34% at 20 h. The study was carried out tocheck the ability of PEC beads to release the vancomycin HCl in the presence of rat cecal content medium resembling thephysiological environment of colon. The results for this ex vivo revealed that optimized formulations are susceptible tocolonic enzymes released from rat cecal contents. The significance of differences was evaluated by analysis of variance.